MEMBANGUN LITERASI SAINS SISWA SD MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA MATERI “INI KHAS DAERAHKU - Hamidah Yuliyana; Hani Handayani; Asep Nurhuda (STKIP Subang, 2026)
This study examines the use of the Make A Match learning model to improve science literacy in fourth grade elementary students on the topic